Involvement of testicular N-glycoproteome heterogeneity in seasonal spermatogenesis of the American mink (Neovison vison) - Zhang, Yufei; Xu, Baozeng (Frontiers in Veterinary Science, 2022)
Spermatogenesis in the American mink is characterized by an annual cycle of transition involving completely inactive and fully activated stages. N-glycosylation of proteins has emerged as an important regulator as it affects protein folding, secretion, degradation, and activity. However, the involvement of protein N-glycosylation in seasonal spermatogenesis of the American mink remains unclear. In the present study, we established a proteome-wide stoichiometry of N-glycosylation in mink testes at various phases of spermatogenesis using N-linked glycosylated-peptide enrichment in conjunction with liquid chromatography-tandem mass spectrometry analysis. A total of 532 N-glycosylated sites matching the canonical Asn-X-Ser/Thr motif were identified in 357 testicular proteins. Both the number of glycoproteins and the sites of N-glycosylated proteins in mink testes were highly dynamic at different stages. Functional analyses showed that testicular proteins with different N-glycosylation might play a vital role in spermatogenesis by affecting folding, distribution, stability, and activity. Overall, Our data suggest that the dynamics of N-glycosylation of testicular proteins are indispensable for seasonal spermatogenesis in the American mink.